Continuous hydrogenation of glucose with ruthenium on carbon nanotube catalysts. Issue 2 (23rd October 2014) - Aho, Atte; Roggan, Stefan; Eränen, Kari; Salmi, Tapio; Murzin, Dmitry Yu.
Abstract : Continuous hydrogenation of glucose to sorbitol was studied in an experimental set-up with parallel screening multiphase reactors. Abstract : Continuous hydrogenation of glucose to sorbitol was studied in an experimental set-up with parallel screening multiphase reactors. After investigating a range of reaction parameters, the suitable conditions for catalyst screening were found to be 130 °C, 2.0 ml min −1 flow rate and 0.2 mol L −1 glucose concentration. The hydrogen pressure was kept at 20 bar under all reaction conditions investigated. A slate of different ruthenium supported on carbon (active carbon and carbon nanotubes) catalysts was screened. All catalysts showed high (>97.4%) selectivities to sorbitol, while activity and stability varied. Long-term evaluation of the two best catalysts was performed over a 100 h period.